Primary versus secondary closure of stoma reversal skin wound: randomized controlled trial - Akbar, Ismail; Javed, Zanib; Batool, Naila (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the efficacy of primary versus secondary closure of stoma reversal skin wound in terms of wound infection. Method: The study was conducted at Surgical B Unit of Ayub Teaching Hospital, Abbottabad, Pakistan, from January 1 to December 31, 2020, and comprised adult patients of either gender undergoing stoma reversal. The patients were randomised into primary closure group A and secondary closure group B. Surgical procedure was similar in both the groups except the skin closure technique. In group A, skin was closed with interrupted polypropylene sutures, while in group B, wound was dressed with saline-soaked gauze daily using aseptic technique and was allowed to heal by secondary intention or delayed primary closure latter on. Postoperatively, the wound was assessed for infection till 30th postoperative day or complete wound healing. Data was analysed using SPSS 16. Results: Of the 50 patients, 35(70%) were males and 15(30%) were females. The overall mean age was 28±1.65years. There were 25(50%) patients in each of the two groups. There were 19(76%) males and 6(24%) females in group A with a mean age of 32±2.8years. There were 16(64%) males and 9(36%) females in group B with a mean age of 23±3.5years. Overall, 10(20%) patients had wound-site infections; 9(36%) in group A versus 1(4%) in group B (p=0.005). Frequency of wound infection with respect to gender, type of stoma and length of hospital stay was not significant (p>0.05). Conclusion: Secondary skin closure was found to be associated with significantly reduced wound infection rate after stoma reversal. Clinical Trial Number: NCT04785404. Link; https://clinicaltrials.gov/ct2/show/NCT04785404 Key Words: Stoma reversal, Primary closure, Secondary closure, Wound infection, Ileostomy, Colostomy.